Evaluasi budidaya dan potensi pengembangan kopi di Kabupaten Nabire Provinsi Papua Tengah - Hwat Dasnarebo, Simson Semuel; Prabawardani, Saraswati; Ramandey, Yohanes; Suparno, Antonius; Wibawati, Zarima (Cassowary, 2025)
ABSTRACT: This research aims to study the cultivation of coffee plants, specifically Robusta coffee (Coffea canephora), grown by farmers in Kampung Air Mandidi and Kampung Samabusa. Coffee cultivation began in 1998, using local seedlings obtained from previous farmers. As a refreshing beverage, coffee is important in daily life and local culture. Although coffee cultivation is not the main occupation for farmers, it shows potential for further development. This study also observed that farmers implement mixed planting systems or agroforestry, where coffee plants are grown alongside other crops such as bananas, durians, and corn. This agroforestry approach not only diversifies agricultural yields but also reduces the risk of pest attacks and enhances the sustainability of the agricultural ecosystem. The research findings indicate that despite challenges in the socialization and marketing of coffee products in the area, the cultivation system applied by the farmers contributes to their overall success and well-being. This research emphasizes the importance of promoting sustainable cultivation practices and supporting farmers facing market challenges to increase local coffee production. Additionally, it highlights the significance of coffee not only as an agricultural product as well as a source of refreshment in the community.